Co-design of harm reduction materials for people who inject drugs to implement research findings - Deborah Hussey; Zoe Trinder-Widdess; Cassie Dee; Darren Bagnall; Tatty Bojangles; Joanna May Kesten (BMC, 2019)
Abstract Background Equipment used by people who inject drugs (PWID) either has a needle which is fixed to the syringe or can be detached and replaced. Detachable low dead space syringes (LDSS) have been developed, with less space between the needle and plunger (referred to as dead space) than traditional detachable equipment. This equipment can help protect PWID from harm of infection as less blood is transferred if equipment is shared. Our previous research found that detachable LDSS are likely to be acceptable to PWID, and we produced recommendations for their introduction in needle and syringe programmes (NSP) in the United Kingdom (UK). We held a national stakeholder meeting to discuss how to accelerate the pace and scale of the rollout and uptake of detachable LDSS. This commentary reflects on the involvement of PWID as co-designers of harm reduction materials to implement these research findings in a way that supports the uptake of LDSS equipment by NSP and service users. We present the user-centred design process, peer reflections on the project, and lessons learnt by the team working with the peers. Main body Peers and stakeholders translated the research into easy to understand messages following a consultation with NSP across the UK. Working with Linnell Publications over three workshops, peers selected their preferred design style and informed the language, messages, and overall look of the designs. The peers ensured the designs avoided images and language with negative connotations, humour, and unequivocal language. Peers said that they found the process enjoyable and informative-leading to increased awareness of harm reduction practices. The facilitators took steps to ensure the views of the peers were heard throughout. They reflected on the importance of involving PWID meaningfully throughout the project. Without the peers, the designs would be less effective and engaging to their target audience. Conclusion We conclude that placing peers at the heart of this research implementation project was essential to ensure the materials are appropriate and engaging and do not stigmatise or alienate the intended audience unintentionally. We recommend that others planning similar work include peers within the entire project to support their meaningful contribution.